2018
DOI: 10.3390/nano8030165
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laminin Surface Modification of Electrospun Silica Nanofiber Substrate on Neuronal Tissue Engineering

Abstract: In this study, we first synthesized a slow-degrading silica nanofiber (SNF2) through an electrospun solution with an optimized tetraethyl orthosilicate (TEOS) to polyvinyl pyrrolidone (PVP) ratio. Then, laminin-modified SNF2, namely SNF2-AP-S-L, was obtained through a series of chemical reactions to attach the extracellular matrix protein, laminin, to its surface. The SNF2-AP-S-L substrate was characterized by a combination of scanning electron microscopy (SEM), Fourier transform–infrared (FTIR) spectroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 57 publications
(83 reference statements)
0
28
0
Order By: Relevance
“…Moreover, lack of controllability on the orientation of adsorbed cell‐adhesive biomolecules is another drawback that highly decreases the efficiency of this method . Chen et al investigated the effects of physical adsorption and covalent attachment of laminin molecules on the surface of electrospun silica nanofibrous scaffolds (SNF2) . The physical coating was performed by immersing in laminin solution.…”
Section: Surface Modification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, lack of controllability on the orientation of adsorbed cell‐adhesive biomolecules is another drawback that highly decreases the efficiency of this method . Chen et al investigated the effects of physical adsorption and covalent attachment of laminin molecules on the surface of electrospun silica nanofibrous scaffolds (SNF2) . The physical coating was performed by immersing in laminin solution.…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…The chemical bonding was carried out by soaking in an ethanol solution with 3 m (3‐aminopropyl)triethoxysilane (APTS), then incubation of the APTS‐modified SNF2 in a cross‐linker solution, sulfo‐(succinimidyl‐4‐[ N ‐maleimidomethyl]cyclohexane‐1‐carboxylate) (SMCC), and finally immersion of the APTS–SMCC‐modified SNF2 in laminin solution. They confirmed that covalent attachment of laminin leads to constant neuritis extension and prolonged biochemical stimulation of PC12 cells, while the physical coating of laminin onto the surface of substrates failed to provide the same effect ( Figure A,B) …”
Section: Surface Modification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compatibility of oxidized silicon or silicon nitride for in vitro functional studies on neurons has been already reported, nevertheless, this is the first study to report compatibility with hCPs [50]. Furthermore, contrary to other studies employing silicon uncoated surfaces, we used surface topographies coated with laminin to optimize cell adhesion as also been reported by others [51][52][53]. In addition, these results demonstrate that our silicon micropillar arrays can be functionalized according to the cells' needs.…”
Section: Culturing Human Cortical Progenitors On Vertically-aligned Smentioning
confidence: 69%
“…We have previously demonstrated a multi-step chemical reaction process to modify the surface of a silica nanofiber for assisting cell attachment and enhancing neuronal cell growth and differentiation [ 30 ]. To explore the possibility of grafting RGD onto silica nanofibers without introducing any cross-linking agents, we identified a published silica-binding protein (SB) [ 31 ] that could be used for one-step anchoring of RGD onto silica surfaces.…”
Section: Introductionmentioning
confidence: 99%